2022
DOI: 10.3389/fnsys.2022.984406
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the cerebellum in migraine

Abstract: Migraine is a disabling neurological disease characterized by moderate or severe headaches and accompanied by sensory abnormalities, e.g., photophobia, allodynia, and vertigo. It affects approximately 15% of people worldwide. Despite advancements in current migraine therapeutics, mechanisms underlying migraine remain elusive. Within the central nervous system, studies have hinted that the cerebellum may play an important sensory integrative role in migraine. More specifically, the cerebellum has been proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 249 publications
1
9
0
Order By: Relevance
“…Consequently, the observed gray matter changes in the cerebellum could be linked to variations in pain severity, and mirroring patterns observed in migraines (Ruscheweyh et al., 2014). Earlier studies have indicated both decreases and increases in cerebellar gray matter volume among individuals with migraines, consistent with the findings from our included studies involving TTH patients (Wang, Tutt, et al., 2022). To gain a more comprehensive understanding of the role of the cerebellum in TTH, future preclinical and clinical studies on cerebellar changes in individuals with TTH should be conducted.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the observed gray matter changes in the cerebellum could be linked to variations in pain severity, and mirroring patterns observed in migraines (Ruscheweyh et al., 2014). Earlier studies have indicated both decreases and increases in cerebellar gray matter volume among individuals with migraines, consistent with the findings from our included studies involving TTH patients (Wang, Tutt, et al., 2022). To gain a more comprehensive understanding of the role of the cerebellum in TTH, future preclinical and clinical studies on cerebellar changes in individuals with TTH should be conducted.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the increased connectivity between the cerebellum and other regions could be indicative of a dysfunctional negative feedback loop in which the thalamus is not sensing the inhibitory signal (31). These connectivity results could be indicative of the importance of the cerebellum in the modulation of migraine possibly through the modulation of calcitonin gene-related peptide (CGRP) (11, 14). CGRP modulates nociception and assists in the onset of migraine, and thus it might play a role in reshaping connectivity and stabilizing synapses in the cerebellar circuitry (33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…Critically, although the cerebellum has an important role in pain processing (14), to our knowledge no study of structural connectivity using tractography in migraine has included it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, while C2 GON blockade has demonstrated some superiority over distal GON blockade for the treatment of migraine, we do not anticipate it having a significant impact on clinical practice. However, the fact that this blockade can cause cerebellar side effects in migraine patients may support further examination of the role of residual cerebellum in migraine pathophysiology, potentially leading to new target regions for pharmacological interventions [16][17][18] . This potential avenue of research could open up new horizons for treating migraine and could be seen as the most important benefit of C2 GON blockade for migraine patients.…”
Section: Submerged Portion Of C2 Gon Blockadementioning
confidence: 99%